2007
DOI: 10.2460/ajvr.68.7.788
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protection against systemic infection and disease from experimental bovine viral diarrhea virus type 2 infection by use of a modified-live noncytopathic type 1 vaccine in calves

Abstract: The modified-live BVDV type 1 vaccine protected against systemic infection and disease after experimental challenge exposure with BVDV type 2. The vaccine protected calves against infection and viremia and prevented infection of target lymphoid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Viremia was detected between 3 and 9 dpi and peaked at 6 dpi in parallel with hyperthermia and the highest intensity of clinical signs, highlighting the pathogenic action of the virus. Most authors report that, as observed here, experimental infection of calves with ncp BVDV‐1 gives rise to transient viremia, which resolves about 12 days after infection (Nuttall et al., ; Castrucci et al., ; Howard et al., ; Bruschke et al., ; Archambault et al., ; Charleston et al., ; Brackenbury et al., ; Kelling et al., ).…”
Section: Discussionmentioning
confidence: 54%
“…Viremia was detected between 3 and 9 dpi and peaked at 6 dpi in parallel with hyperthermia and the highest intensity of clinical signs, highlighting the pathogenic action of the virus. Most authors report that, as observed here, experimental infection of calves with ncp BVDV‐1 gives rise to transient viremia, which resolves about 12 days after infection (Nuttall et al., ; Castrucci et al., ; Howard et al., ; Bruschke et al., ; Archambault et al., ; Charleston et al., ; Brackenbury et al., ; Kelling et al., ).…”
Section: Discussionmentioning
confidence: 54%
“…We identified 12 BVDV trials from 8 studies for inclusion in the analysis . Table S1 summarizes the studies that were reviewed and analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Rectal temperatures in response to the BVDV exposure reported by Burciaga-Robles et al (2010b) were approximately 0.3 to 0.5°C greater than those of nonexposed calves during a period from 36 to 72 h after MH challenge. In a BVDV type 2 challenge, Kelling et al (2007) reported that nonvaccinated animals had greater rectal temperatures on d 9 to 11 after intranasal challenge compared with a vaccinated group. Calves challenged with noncytopathic type 1 BVDV (Gånheim et al, 2005) had a mild fever (>39.5°C) from d 1 through 5 after viral inoculation compared with nonchallenged controls.…”
Section: Figurementioning
confidence: 98%